The key role of magnesium sulfate in the management of organophosphorus pesticide poisoning: a scoping literature review - Zahra Nekoukar; Homa Talabaki; Zakaria Zakariaei; Mahdi Mesri; Hossein Azadeh (Clinical and Experimental Emergency Medicine)
Organophosphorus agents are easily absorbed via respiratory, gastrointestinal, and dermal routes, and inhibit the acetylcholinesterase (AChE) enzyme, which is responsible for the majority of toxicity caused by organophosphates in the body. A comprehensive search was conducted across three prominent databases (Google Scholar, PubMed, and Science Direct) to identify relevant articles. The search focused on the keywords “MgSO4” or “magnesium sulfate” in conjunction with “organophosphate” or “organophosphate poisoning.” Inhibition of the AChE results in the accumulation of acetylcholine in synapses and the stimulation of cholinergic receptors. As several studies have shown that magnesium sulfate (MgSO4) can inhibit the release of acetylcholine in the central and peripheral sympathetic and parasympathetic synapses, this study reviews the role of MgSO4 in the treatment of organophosphorus poisoning. The intravenous administration of MgSO4 exhibits favorable tolerability and clinical efficacy in alleviating cardiac toxicity associated with organophosphorus poisoning.